DIGITAL GAMBLING AND MORAL DECLINE: FAMILY RESILIENCE FROM AN ISLAMIC HUMANISTIC APPROACH - Armi Agustar; Aslati; Adji Pratama Putra; Silawati; Mutasir (Khazanah: Jurnal Studi Islam dan Humaniora, 2025)
This study examines the implications of online gambling practices on family resilience through the ethical-humanistic framework of maqāṣid al-sharī‘ah. As a contemporary social phenomenon in the digital era, online gambling not only affects families’ economic stability but also undermines their moral integrity, psychological well-being, and spiritual harmony. Using a qualitative, literature-based approach, this study analyzes classical and contemporary Islamic scholarly works along with secondary data on the social consequences of online gambling, using descriptive and interpretive analysis. The findings indicate that online gambling poses serious challenges to the core objectives of maqāṣid al-sharī‘ah, specifically the preservation of religion (ḥifẓ al-dīn), reason (ḥifẓ al-‘aql), wealth (ḥifẓ al-māl), and progeny (ḥifẓ al-nasl). Rather than serving as a basis for formal legal decisions, the maqāṣid al-sharī‘ah in this study serves as an ethical lens for interpreting the broader social impacts of online gambling, including the erosion of family roles, moral degradation, and increased economic vulnerability within households. This study underscores the importance of strengthening maqāṣid-based values ​​as a foundation for preventive, educational, and social interventions aimed at maintaining family resilience. This study contributes to the development of a more responsive and interdisciplinary Islamic ethical discourse in addressing the social challenges of the digital age.